We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
178
1
avatar+4684 

Help.

 Feb 16, 2018
 #1
avatar+99580 
+1

 

 

 

y  =  1/x     y  =  3/x

 

Note that  if x  =  1   

 

y   in the first function  = 1/1  = 1

 

But y in the second function becomes  3/ 1  =  3

 

So....the second function vertically "stretches" the  first function by a factor of 3

 

And the  "-4"  at the end   will shift this y = 3/x   down 4 units 

 

So.....the third answer is correct

 

cool cool cool

 Feb 16, 2018

10 Online Users

avatar
avatar